Banks' Reserve Management, Transaction Costs, and the Timing of Federal Reserve Intervention - Bertola, Giuseppe (IMF Working Papers; Working Paper, 2000)
We use daily data on bank reserves and overnight interest rates to document a striking pattern in the high-frequency behavior of the U.S. market for federal funds: depository institutions tend to hold more reserves during the last few days of each 'reserve maintenance period,' when the opportunity cost of holding reserves is typically highest. We then propose and analyze a model of the federal funds market where uncertain liquidity flows and transaction costs induce banks to delay trading and to bid up interest rates at the end of each maintenance period.